2018
DOI: 10.1371/journal.pone.0201622
|View full text |Cite
|
Sign up to set email alerts
|

Photo-based External Quality Assessment of Malaria rapid diagnostic tests in a non-endemic setting

Abstract: IntroductionIn non-endemic settings, expertise in malaria microscopy is limited and rapid diagnostic tests (RDTs) are an adjunct to malaria diagnosis.AimWe performed an External Quality Assessment (EQA) on reading and interpretation of malaria RDTs in a non-endemic setting.MethodsParticipants were medical laboratories in Belgium and the Grand Duchy of Luxembourg using malaria RDTs; they received (i) 10 high-resolution photographs presenting test line combinations of RDTs with interpretations listed in a multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
4
8
0
Order By: Relevance
“…13 In studies of malaria RADT, weak positive test bands consistently correlate with lower sensitivity. [11][12][13] Our study confirms these findings for SARS-CoV-2 RADT, and provides evidence for a simple and effective corrective intervention.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…13 In studies of malaria RADT, weak positive test bands consistently correlate with lower sensitivity. [11][12][13] Our study confirms these findings for SARS-CoV-2 RADT, and provides evidence for a simple and effective corrective intervention.…”
Section: Discussionsupporting
confidence: 82%
“…In this prospective field evaluation of self-performed SARS-CoV-2 RADT in an intended-use setting, the accuracy of signal interpretation was proportional to test band intensity, and was extremely low for tests with weak bands. An evidence-based Modified Quick Reference Guide improved signal interpretation by untrained workers to a level of accuracy comparable to that of professional technologists for other RADTs, 11,12 but did not have a major impact on the proper execution of procedural steps. Repeated self-testing was associated with improved signal interpretation, though the effect was less apparent with tailored instructions as initial accuracy was already high.…”
Section: Discussionmentioning
confidence: 93%
“…However, malaria microscopy is a labour intensive method whose quality strongly relies on well experienced personal, and in countries where relatively few cases of malaria are seen it may be difficult to maintain required levels of training also considering of the large number of laboratory staff who alternate in emergency services. Some studies have shown that prompt laboratory malaria diagnosis may be particularly challenging during outof-office hours when competent microscopists may not be available [8][9][10]. In a study conducted in Portugal half of all malaria smears were performed out-of hours (i.e., other than 9-17 Monday to Friday) but accounted for 61% of malaria diagnosis [11].…”
mentioning
confidence: 99%
“…In some hospital laboratories in United Kingdom (UK) as well as in other European countries, after-hours diagnosis of malaria is performed using only immunochromatography-based malaria rapid diagnostic tests (RDTs) [8,12]. A large survey conducted in Belgium and Luxembourg has also shown that one third of participant laboratories used RDTs alone for malaria diagnosis although this is not a recommended practice [9]. Although RDTs are rapid, easy to use and sensitive for P. falciparum, they lack sensitivity at low parasite density, fail to identify a large number of non-falciparum malaria, do not allow parasite quantification, are prone to some errors in reading and interpreting test lines and result in false negative malaria diagnosis when P. falciparum with Histidine Rich Protein 2 (HRP2)-deletion is involved [6,9,10,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation